Insulin degludec/liraglutide versus its monotherapy on T2D patients: A lifetime cost-utility analysis in China - Han, Guangxin; Hu, Shanshan; Zhang, Xiaoning; Qiu, Zhikun; Huang, Zhe (Frontiers in Pharmacology, 2022)
Introduction: IDegLira (brand name Xultophy) is a novel fixed ratio combination of insulin degludec and liraglutide for type 2 diabetes (T2D) patients. This study aimed to investigate the lifetime cost-effective value of IDegLira compared with its single component (Degludec or Liraglutide) and to explore the suitable annual cost of IDegLira if necessary. Methods: UKPDS OM2 was applied to determine the long-term quality-adjusted life years (QALYs) and total costs. The efficacy data that were inputted into the model were synthesized from 6 randomized clinical trials (RCTs) that directly assessed the clinical benefit of IDegLira and its components in the treatment of uncontrolled T2D patients. The economic results were examined by one-way sensitivity analysis (OSA) and probabilistic sensitivity analysis (PSA). Further price reduction of IDegLira was investigated by binary search. Results: The IDegLira, IDeg, and Lira yielded 11.79 QALYs, 11.62 QALYs, and 11.73 QALYs and total cost of $20281.61, $3726.76, and $11941.26, respectively. The incremental cost-utility ratio (ICUR) of IDegLira versus IDeg was $99464.12/QALYs, and the ICUR of IDegLira versus Lira was $143348.26/QALYs, which indicated that IDegLira was not a cost-effective therapy for T2D patients compared with its components at the current price from a Chinese national healthcare system perspective. Base case results were robust to OSA and PSA. A further binary search showed that IDegLira appears to only be cost-effective if the annual cost of IDegLira is decreased by 58% when IDeg is considered as a reference, or by 30.57% when Lira is considered as a reference. Conclusion: In conclusion, IDegLira appears to not be cost-effective when compared with the current prices of IDeg or Lira for T2D patients in China. However, after the binary search, IDegLira appears to only be cost-effective if the annual cost of IDegLira is decreased 58% when IDeg is considered as a reference, or by 30.57% when Lira is considered as a reference.